EFEKTIVITAS PROGRAM PERWIRA BHABINKAMTIBMAS POLRES BOGOR KOTA DALAM PENANGANAN PERKARA MELALUI ALTERNATIF PENYELESAIAN SENGKETA - Didik Supriyoko; Ujang Bahar; Mul yadi (JURNAL HUKUM DE'RECHTSSTAAT, 2016)
The method used in this research is a normative juridical research with comparative law. This study will be a descriptive analysis will provide an overview of the Implementation Program of Bogor City Police Officer Bhabinkamtibmas by virtue Kapolri No.Pol: B / 3022 / XII / 2009Sdeops Date December 14, 2009 on the Handling of Cases Through the Alternative Dispute Resolution (ADR). The program is named after the latest Police Officer Bhabinkamtibmas. The program is a pilot project. This program will be applied in the future to another police station to an extent Polsek.Dengan the Bhabinkamtibmas officers who have members from a wide range of functions is expected to prevent the disruption of security and public order as well as to resolve conflicts early horizontal. The role and function Bhabinkamtibmas members in each region will be further optimized. Bhabinkamtibmas officer team will be down directly in the community to help solve the problems of citizens. Thus, each issue should not be resolved through legal channels, but through mediation and approach officials with the public. The formation of a team of officers Bhayangkara Trustees Public Order and Safety in the City Police Bogor, West Java, a pilot project, particularly for the police station in West Java. The team of eight people who have received training and certification from the National Mediation Centre. The team is a kind of ad hoc team, which is responsible to the Chief of Police and Officer Team members Bhabinkamtibmas of some police functions, not only the function of public guidance. The conclusion from this study is the Program Implementation in Bogor Police Officer Bhabinkamtibmas City and yet not maximum impact on increasing public perception of the police. In terms of implementation, it appears less optimal competence of officers in the police station and police station level. Instructive culture within the police adopted a policy of military norms Officer Program Bhabinkamtibmas seen by officers in the field more as a mere 'implementation of new tasks' rather than the 'improvement of quality of service'.